THE DYNAMICS OF SCHOOL PRINCIPALS' MANAGERIAL COMPETENCE AND ITS IMPACT ON TEACHER PERFORMANCE: A CASE STUDY AT SIT BINA BANGSA, SERANG CITY - Nana Surya Permana; Budi Ilham Maliki (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to describe the dynamics of principals' managerial competencies and analyze their impact on teacher performance at the Bina Bangsa Integrated Islamic School (SIT) in Serang City. These competencies include creating a healthy organizational climate, effective decision-making, and empowering human resources in line with Islamic values. This study used a qualitative case study approach, with the principal as the primary informant and teachers as supporting informants. Data were collected through interviews, observations, and document reviews. The results indicate that principals possess strong competencies in program planning, academic supervision, and relationship and communication management. However, several challenges remain, such as a lack of ongoing training in strategic management and gaps in internal conflict management. The impact is seen in increased teacher professionalism, motivation, and involvement in decision-making. Teacher performance improves significantly when principals implement participatory, responsive, and appreciative leadership. This study recommends strengthening principals' professional development programs, developing measurable performance indicators, and implementing collaborative leadership based on ethics, educational vision, and spiritual values to build an organizational culture that supports sustainable educational quality